Korupsi, Hadiah, dan Hibah dalam Hukum Positif dan Fikih Kontemporer: Corruption, Gifts, and Grants in Positive Law and Contemporary Fiqh - Nurahmad; Misbahuddin; Shuhufi (Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study examines the conceptual and practical distinctions between corruption, gifts, and grants within Indonesia’s legal framework while analyzing how contemporary Islamic jurisprudence interprets similar practices that may lead to unethical influence. This study's goal is to address the central problem of determining when a gift becomes an illicit benefit, how moral considerations shape decision-making by public officials, and why the convergence of ethical and legal standards is essential for maintaining public trust. Using a normative juridical method, the study reviews legal norms, scholarly opinions, ethical principles, and selected cases to understand how rules and moral reasoning interact. The findings of this study indicate that Indonesian positive law clearly distinguishes corruption, grants, and gifts based on the relationship to public office, conflicts of interest, and transparency obligations as regulated under the Anti-Corruption Law and KPK regulations. In contrast, contemporary Islamic jurisprudence evaluates grants and gifts given to public officials as potentially constituting risywah when they are accompanied by an intention to influence decisions or result in social injustice. Comparative analysis demonstrates that the legal-formal approach of positive law and the moral-transcendental approach of Islamic jurisprudence are not contradictory but complementary. Both legal systems converge on the shared objective of safeguarding public integrity, justice, and the public interest. The integration of normative legal mechanisms with ethical principles derived from maqāṣid al-sharī‘ah produces a more comprehensive framework for corruption prevention. The novelty of this research lies in the formulation of an integrative analytical model that bridges legal certainty with moral consciousness. This model reframes the regulation of gratification not merely as an administrative obligation but as an instrument for cultivating ethical integrity among public officials. Accordingly, the study contributes both theoretically to the development of integrative legal scholarship and practically to the advancement of morally grounded anti-corruption policies in modern society.